Answer:
ok so this problem you are basically just rearranging it. you're going to want y by itself.
Explanation:
let's start with the original equation: 5-y=1/3x +12
so first you have to move the five over, so you subtract 5 from both sides. -y=1/3x+12-5
then you subtract the 5 from the twelve since they're like terms: -y=1/3x+7
and finally you have to move the negative over. when you move the negative think of it like dividing negative one from both sides, everything on the other side has to get the negative.
so we're left with y=-1/3x-7
I hope this helps!